Implications of clinical simulation in motivation for learning: scoping review - Barbara Casarin Henrique-Sanches; Dario Cecilio-Fernandes; Raphael Raniere de Oliveira Costa; Rodrigo Guimarães dos Santos Almeida; Federico Ferrero Etchegoyen; Alessandra Mazzo (Einstein (São Paulo), 2024)
ABSTRACT Objective: To identify, synthesize, and analyze the scientific knowledge produced regarding the implications of using clinical simulation for undergraduate nursing or medical students' motivation for learning. Methods: The search for articles was conducted between July 28 and August 3, 2022, on the PubMed/MEDLINE, Scopus, Web of Science, and SciELO databases. The following was used for the search: P - undergraduate students attending Nursing or Medicine courses; C - motivation for learning, and C - skills and clinical simulation laboratory. The following research question guided the study: “What are the implications of clinical simulation on the motivation for learning of undergraduate students of nursing and medicine?” Of the 1,783 articles found, 13 were included in the sample for analysis. All stages of the selection process were carried out by two independent evaluators. The results were presented as charts and a discursive report. Results: The studies analyzed indicated the beneficial effects of clinical simulation on students' motivation, in addition to other gains such as competencies, technical and non-technical skills, knowledge, belonging, autonomy, clinical judgment, critical and reflective thinking, self-efficacy and decreased anxiety, self-management, and improvements in learning and learning climate. Conclusion: Clinical simulation provides a positive learning environment favorable to the development of technical and interpersonal skills and competencies, and raising the level of motivational qualities.